The development of an in situ hybridisation technique to determine the gene expression patterns of UDP-Glucose dehydrogenase, pyrophosphate-dependent phosphofructokinase and UDP-Glucose pyrophosphorylase in sugarcane internodal tissues - Ramoutar, Rakeshnie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.